2014
DOI: 10.15406/jpnc.2014.01.00007
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics and Synbiotics in Necrotizing Enterocolitis: Where Are We?

Abstract: Preterm neonates are susceptible to complications, including necrotizing enterocolitis, a leading cause of morbidity and mortality. Probiotics are live microorganisms, that when administered in adequate amounts, confer a health benefit to the host. Current evidence suggests that probiotics are effective in decreasing the incidence of NEC in preterm infants. Nondigestible oligosaccharides 'prebiotics' have a positive impact on the micro biota and represent another potential preventative therapy. The combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 50 publications
(58 reference statements)
0
11
0
Order By: Relevance
“…Recently, Sawh et al concluded that administration of probiotics may prevent severe NEC in infants with a birth weight < 2500 g but did not recommend for babies with a birth weight < 1000 g [107]. Reviewed literature suggested administration of probiotics in premature infants for prevention of NEC, however the current evidence are not conclusive due to the heterogeneity of probiotic formulations (single or multiple-strains of probiotics), diverse doses (10 5 to 10 10 cfu/ml) and duration of treatment [108]. Based upon reviewed literature routine use of probiotics in the preterm infant is not be recommended due to many uncertainties such as the mechanisms of action of probiotics, health effects of employed probiotics, forms of microbial adaptations and ecological consequences [109].…”
Section: Safety Of Probiotics For Preterm Infantsmentioning
confidence: 99%
“…Recently, Sawh et al concluded that administration of probiotics may prevent severe NEC in infants with a birth weight < 2500 g but did not recommend for babies with a birth weight < 1000 g [107]. Reviewed literature suggested administration of probiotics in premature infants for prevention of NEC, however the current evidence are not conclusive due to the heterogeneity of probiotic formulations (single or multiple-strains of probiotics), diverse doses (10 5 to 10 10 cfu/ml) and duration of treatment [108]. Based upon reviewed literature routine use of probiotics in the preterm infant is not be recommended due to many uncertainties such as the mechanisms of action of probiotics, health effects of employed probiotics, forms of microbial adaptations and ecological consequences [109].…”
Section: Safety Of Probiotics For Preterm Infantsmentioning
confidence: 99%
“…Subsequent enteral feeding and environmental factors affects colonization. The pattern changes according to the type of delivery (spontaneous vaginal delivery/ caesarean section), maturity of baby, feeding (human milk / formula), administration of antibiotics and drugs acting on gastrointestinal tract [8]. Newborns delivered vaginally have more Bifidobacterium and Lactobacillus species and colonization with these beneficial microorganisms [9].…”
Section: Introductionmentioning
confidence: 99%
“…Colonization with non-pathogenic diverse organisms such as Bifidobacteria and Lactobacillus is seen in healthy term babies [2]. The process of colonization in preterm and low birth weight is delayed, less diverse and with a pattern predominating pathogenic microbiome such as Staphylococci, coliforms, and bacteroids [8,9]. Bifidobacterium and Lactobacillus are the principal kinds of commensal bacteria found in breast fed babies [2,9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations